Membrane lipid therapy: Modulation of the cell membrane composition and structure as a molecular base for drug discovery and new disease treatment. (July 2015) - Escribá, Pablo V.; Busquets, Xavier; Inokuchi, Jin-ichi; Balogh, Gábor; Török, Zsolt; Horváth, Ibolya; Harwood, John L.; Vígh, László
Abstract: Nowadays we understand cell membranes not as a simple double lipid layer but as a collection of complex and dynamic protein–lipid structures and microdomains that serve as functional platforms for interacting signaling lipids and proteins. Membrane lipids and lipid structures participate directly as messengers or regulators of signal transduction. In addition, protein–lipid interactions participate in the localization of signaling protein partners to specific membrane microdomains. Thus, lipid alterations change cell signaling that are associated with a variety of diseases including cancer, obesity, neurodegenerative disorders, cardiovascular pathologies, etc. This article reviews the newly emerging field of membrane lipid therapy which involves the pharmacological regulation of membrane lipid composition and structure for the treatment of diseases. Membrane lipid therapy proposes the use of new molecules specifically designed to modify membrane lipid structures and microdomains as pharmaceutical disease-modifying agents by reversing the malfunction or altering the expression of disease-specific protein or lipid signal cascades. Here, we provide an in-depth analysis of this emerging field, especially its molecular bases and its relevance to the development of innovative therapeutic approaches.